Updates in the Diagnosis and Treatment of Vasculitis 2013
DOI: 10.5772/55189
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Causes of Vasculitis

Abstract: Table 1. Names and definitions of vasculitides adopted by the Chapel Hill Concensus Conference on the Nomenclature of Systemic Vasculitis Updates in the Diagnosis and Treatment of Vasculitis 132

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 122 publications
(129 reference statements)
2
7
0
Order By: Relevance
“…The majority of patients were male representing 83%, and the remaining 17% were female patients. Similar findings were previously reported [ 6 , 13 , 32 ]. The higher incidence of the young, male IE patients in our study can be correlated to the high number of injection drug users (IDUs), which is considered a problem related mainly to the young males in our Egyptian society [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The majority of patients were male representing 83%, and the remaining 17% were female patients. Similar findings were previously reported [ 6 , 13 , 32 ]. The higher incidence of the young, male IE patients in our study can be correlated to the high number of injection drug users (IDUs), which is considered a problem related mainly to the young males in our Egyptian society [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…In 2018, Asgeirsson et al reported that S. aureus is the foremost cause of IE where it comprises about 15–40% of all IE cases worldwide [ 4 ]. IE is primarily caused by bacteria or fungi that may progress to serious cardiac complications [ 6 ]. IE is typically characterized by the development of “cauliflower-like” vegetations, consisting of host factors including fibrin, platelets, and bacterial aggregates on the damaged endothelium of heart valves [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients were male representing 83% and the remaining 17% were female patients. Similar findings were previously reported [30, 5, 12]. The higher incidence of IE among the young, male patients is attributed to the predominance of the injection drug users (IDUs), which is considered a problem related mainly to the young males in our Egyptian society [31].…”
Section: Discussionsupporting
confidence: 84%
“…IE is caused principally with bacteria or fungi where serious clinically relevant complications including, damaging of one or more of the heart valves, necrosis of mural endocardium, or sometimes septal defects could occur [5]. Moreover, IE is distinguished by the development of “cauliflower– like” vegetations, consisted of host factors including, fibrin, platelets and bacterial aggregates on the damaged endothelium of heart valves [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous small-vessel vasculitis is classified as idiopathic or secondary due to infection, drugs, connective tissue disease, malignancy, or other diseases. The etiology of secondary vasculitis is challenging to differentiate due to the same cellular component in histology [8]. Additionally, antibodies as autoimmune markers may become positive in infection [2,10].…”
Section: Discussionmentioning
confidence: 99%